AMP-activated protein kinase in the heart: role in cardiac glucose and fatty acid metabolism. (October 2009) - Kewalramani, Girish; Rodrigues, Brian
The stress-signaling protein, AMP-activated protein kinase (AMPK), has emerged as a central regulator of energy metabolism in mammalian cells. Studies over the last decade have identified novel players in the complex regulation of AMPK. Activated AMPK supports the production of energy by controlling vital steps in both glucose and fatty acid metabolism. Myocardial AMPK stimulates glycolysis and promotes glucose entry by influencing specific proteins and glucose transporters. AMPK also facilitates the generation of energy by promoting cardiac fatty acid oxidation. Moreover, through its control of particular candidates (lipoprotein lipase and fatty acid transporter proteins), AMPK has been demonstrated to regulate cardiac fatty acid delivery. AMPK also interacts with additional signaling pathways to induce effects on cell metabolism, protein synthesis and gene expression. In addition to energy generation, evidence is accumulating that AMPK may protect the myocardium against cell death. In this review, we focus on the emerging information regarding the regulation of AMPK, its role in cardiac glucose and fatty acid metabolism and its influence on cell death.